Armenia : World Bank Country Survey FY 2013 - World Bank (Washington, DC, 2017)
This country survey for FY2013 in Armenia was designed to achieve the following objectives: assist the World Bank in gaining a better understanding of how stakeholders in Armenia perceive the Bank; obtain systematic feedback from stakeholders in Armenia regarding: their views regarding the general environment in Armenia, their overall attitudes toward the World Bank in Armenia, overall impressions of the World Bank's effectiveness and results, knowledge and research, and communication and information sharing in Armenia, and perceptions of the World Bank's future role in Armenia; and use data to help inform the Armenia country team's strategy.